The hidden potential of sustainable neighborhoods : lessons from low-carbon communities - Fraker, Harrison (Island Press, 2013)
How do you achieve effective low-carbon design beyond the building level? How do you create a community that is both livable and sustainable? More importantly, how do you know if you have succeeded? Harrison Fraker goes beyond abstract principles to provide a clear, in-depth evaluation of four first generation low-carbon neighborhoods in Europe, and shows how those lessons can be applied to the U.S. Using concrete performance data to gauge successes and failures, he presents a holistic model based on best practices. The four case studies are: Bo01 and Hammarby in Sweden, and Kronsberg and Vauban in Germany. Each was built deliberately to conserve resources: all are mixed-used, contain at least 1,000 units, and have aggressive goals for energy and water efficiency, recycling, and waste treatment. For each case study, Fraker explores the community's development process andgoals and objectives as they relate to urban form, transportation, green space, energy, water and waste systems, and a social agenda. For each model, he looks at overall performance and lessons learned. Later chapters compare the different strategies employed by the case-study communities and develop a comprehensive model of sustainability, looking specifically at how these lessons can be employed in the United States, with a focus on retrofitting existing communities. This whole-systems approach promises not only a smaller carbon footprint, but an enriched form of urban living. The Hidden Potential of Sustainable Neighborhoods will be especially useful for urban designers, architects, landscape architects, land use planners, local policymakers and NGOs, citizen activists, students of urban design, planning, architecture, and landscape architecture.